2020
DOI: 10.1002/jsfa.10458
|View full text |Cite
|
Sign up to set email alerts
|

Industrial freezing effects on the content and bioaccessibility of spinach (Spinacia oleracea L.) polyphenols

Abstract: BACKGROUNDSpinach is well recognized as a functional food owing to its diverse nutritional composition, including polyphenols. Freezing is an efficient preservation method that is used to maintain the physical and nutritional characteristics and extend the shelf life of spinach. The aim of this study was to determine the changes in polyphenols in the samples taken from various production steps of the industrial freezing process of spinach, and to evaluate the bioaccessibility of these bioactive compounds for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
3
12
0
1
Order By: Relevance
“…The literature data agree with these results, although few studies were found under the same processing and freezing conditions in the literature for the studied byproducts. Kamiloglu [33] also studied TPC changes in spinach samples during industrial freezing, suggesting an excellent nutritional value during freezing storage and aligning with the present study data. As previously reported, after the increase in the TPC and antioxidant capacity stage, some losses were registered compared to the fresh forms with M6 in spinach, but a high nutritional value was registered.…”
Section: Monitorization Of Tpc and Antioxidant Activitysupporting
confidence: 89%
See 3 more Smart Citations
“…The literature data agree with these results, although few studies were found under the same processing and freezing conditions in the literature for the studied byproducts. Kamiloglu [33] also studied TPC changes in spinach samples during industrial freezing, suggesting an excellent nutritional value during freezing storage and aligning with the present study data. As previously reported, after the increase in the TPC and antioxidant capacity stage, some losses were registered compared to the fresh forms with M6 in spinach, but a high nutritional value was registered.…”
Section: Monitorization Of Tpc and Antioxidant Activitysupporting
confidence: 89%
“…However, in all cases, a significant improvement of these compounds was verified comparatively with fresh forms. Kamiloglu [33] studied the impact of industrial freezing on spinach polyphenols, suggesting that freezing can be an excellent strategy to preserve these bioactive groups and aligning with the present study results.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Polyphenols from undigested samples were extracted as described previously 20 . Briefly, 2 mL of the sample was treated with 5 mL of 75% aqueous methanol containing 0.1% formic acid.…”
Section: Methodsmentioning
confidence: 99%